The Influence of Implementing an Ecopedagogic-Based Contextual Approach on the Achievement of History Learning Outcomes of Saparua Christian High School Students - Hetharion, Bety D. S.; Matitaputty, Jenny Koce; Kailuhu, Jacomina S.; Tanikwele, Mevi Bozed (Peneliti.net, 2024)
Education in Indonesia is currently faced with demands to be able to produce quality human resources (HR), namely HR who are able to adapt to the current era of globalization. So education is a determining element in the development of human resources. Learning activities are the most important activities in overall efforts to improve the quality of education. This is because it is through good learning activities that educational goals will be achieved thereby influencing student learning outcomes which are an indicator of success in the learning process. The problem faced by teachers is the teacher's ability to design learning tools by paying attention to the environment as a learning resource. Therefore, before the school year starts, teachers are required to design lesson plans (teaching preparation plans), prepare learning tools/media, and material evaluation materials. The results of the hypothesis test in the table above show the significance value (sig.) or p for the learning model = 0.003. This significance value is smaller than the α value of 0.05, so Ho states